Towards Electrosynthesis in Shewanella: Energetics of Reversing the Mtr Pathway for Reductive Metabolism - Ross, Daniel E.; Flynn, Jeffrey M.; Baron, Daniel B.; Gralnick, Jeffrey A.; Bond, Daniel R. (PloS one, 2011)
Bioelectrochemical systems rely on microorganisms to link complex oxidation/reduction reactions to electrodes. For example, in Shewanella oneidensis strain MR-1, an electron transfer conduit consisting of cytochromes and structural proteins, known as the Mtr respiratory pathway, catalyzes electron flow from cytoplasmic oxidative reactions to electrodes. Reversing this electron flow to drive microbial reductive metabolism offers a possible route for electrosynthesis of high value fuels and chemicals. We examined electron flow from electrodes into Shewanella to determine the feasibility of this process, the molecular components of reductive electron flow, and what driving forces were required. Addition of fumarate to a film of S. oneidensis adhering to a graphite electrode poised at -0.36 V versus standard hydrogen electrode (SHE) immediately led to electron uptake, while a mutant lacking the periplasmic fumarate reductase FccA was unable to utilize electrodes for fumarate reduction. Deletion of the gene encoding the outer membrane cytochrome-anchoring protein MtrB eliminated 88% of fumarate reduction. A mutant lacking the periplasmic cytochrome MtrA demonstrated more severe defects. Surprisingly, disruption of menC, which prevents menaquinone biosynthesis, eliminated 85% of electron flux. Deletion of the gene encoding the quinone-linked cytochrome CymA had a similar negative effect, which showed that electrons primarily flowed from outer membrane cytochromes into the quinone pool, and back to periplasmic FccA. Soluble redox mediators only partially restored electron transfer in mutants, suggesting that soluble shuttles could not replace periplasmic protein-protein interactions. This work demonstrates that the Mtr pathway can power reductive reactions, shows this conduit is functionally reversible, and provides new evidence for distinct CymA:MtrA and CymA:FccA respiratory units.